Natural resources management in African agriculture : understanding and improving current practices [ - Aboud, Abdillahi A.; Place, Frank (CABI, 2002)
This book synthesizes existing information on the adoption of natural resource management investments and strategies (such as soil fertility improvements or erosion control) for agriculture in sub-Saharan Africa. It also critically examines current analtical methods and generates research and policy recommendations. Topics covered include: farmers' objectives and learning processes; willingness and capacity to make long-term investments; economic incentives and the importance of the resource base; and the agroecological, institutional and policy contexts. The book has 22 chapters and a subject index.